2010
DOI: 10.1007/s00417-010-1323-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of optic nerve head topography findings in eyes with non-arteritic anterior ischemic optic neuropathy and eyes with glaucoma

Abstract: Stratus OCT detected significant quantitative differences in RNFL thickness between glaucomatous and NAION eyes, both conditions with hemifield defects. These differences might hold a clue in understanding the processes involved in optic nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 17 publications
2
29
0
2
Order By: Relevance
“…However, other studies have demonstrated a tendency of NAION to involve the superior quadrant of RNFL, particularly in those patients with inferior altitudinal loss [78,79]. In the acute phase, the thickness of the RNFL can be dramatically increased to nearly double the values seen in the unaffected fellow eye [78,79]. In one study of patients with NAION, arteritic anterior ischemic optic neuropathy (AAION) and open angle glaucoma, patients with open angle glaucoma had greater cup size and thinning of the neuroretinal rim than those with NAION and AAION.…”
Section: Non-arteritic Anterior Ischemic Optic Neuropathymentioning
confidence: 99%
See 2 more Smart Citations
“…However, other studies have demonstrated a tendency of NAION to involve the superior quadrant of RNFL, particularly in those patients with inferior altitudinal loss [78,79]. In the acute phase, the thickness of the RNFL can be dramatically increased to nearly double the values seen in the unaffected fellow eye [78,79]. In one study of patients with NAION, arteritic anterior ischemic optic neuropathy (AAION) and open angle glaucoma, patients with open angle glaucoma had greater cup size and thinning of the neuroretinal rim than those with NAION and AAION.…”
Section: Non-arteritic Anterior Ischemic Optic Neuropathymentioning
confidence: 99%
“…One important characteristic of NAION is a small or absent cup in the fellow eye. In most OCT studies, NAION patients have smaller optic cups than controls [75][76][77][78][79]. The reduction in cup size appears to represent an anatomical risk factor for the development of NAION.…”
Section: Non-arteritic Anterior Ischemic Optic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] The high-resolution spectraldomain optical coherence tomography (SD-OCT), also known as the Fourier domain-OCT, can capture microstructures in the rodent retina at up to 100 times the speed of the older timedomain OCT. OCT has been used to approximate optic nerve anatomy by measuring the thickness of the axons of the RGCs, which reside in the retinal nerve fiber layer. [19][20][21][22] In animal studies, OCT has increasingly been used to track anatomic changes of retinal and optic nerve diseases, 18,[23][24][25][26] including Leber's congenital amaurosis, retinal dystrophies, [27][28][29] optic nerve crush, 30,31 N-methyl-D-aspartate (NMDA)-induced retinal ganglion cell loss, 32 optic neuritis, 33 ischemic optic neuropathy, 34,35 and different models of glaucoma. 5,36 In some studies, OCT images are quantitatively or qualitatively comparable to histologic sections at same time points.…”
mentioning
confidence: 99%
“…Существует мнение, что истончение СНВС при ИОН встречается в височном, верхнем и назальном квадрантах, что коррелирует с различными класси-ческими паттернами дефектов полей зрения [8,18]. Выявлено, что толщина СНВС в квадранте, соответ-ствующем неповрежденной полусфере поля зрения, значительно меньше при глаукоме, чем при ИОН [19]. Площадь нейроретинального пояска при глау-коме, определяемая с помощью лазерной сканиру-ющей офтальмоскопии, коррелирует с толщиной СНВС (данные ОКТ) в целом и в, большинстве сек-торов в отличие от исхода ИОН [20].…”
unclassified